The university student movements of Argentina and Uruguay between democracy and dictatorship. Comparisons and connections between both coasts of the Río de La Plata - Seia, Guadalupe A.; González Vaillant, Gabriela (CIAN-Revista de Historia de las Universidades, 2024)
This paper presents a comparative analysis of the reorganization processes of the Argentinean and Uruguayan university student movement between their dictatorships and their democratic transitions. After characterizing the university projects that emerged during their respective dictatorships, the research evaluates novel forms of socialization and politicization that emerged during this strongly authoritarian period, a key element that made possible the reorganization of the student movement. In opposition to the thesis of the decadence of the Latin American student movements during this period, the article reports the existence of a continuum of mobilization that laid the foundations for the emergence of strong movements during democracy. We postulate that the organizational innovation that took place in Uruguay allowed a greater relative weight in the mobilizations and negotiation processes that took place during the transitions to democracy. From a transnational perspective the paper illustrates networks of solidarity and the circulation of ideas and students, albeit it is not possible to identify an unequivocal common identity between movements at Universidad de Buenos Aires and Universidad de la República.